Intranasal Extramucosal Access: A New Access for Lateral Osteotomy in Open Rhinoplasty. Issue 3 (May 2016) - Tellioglu, Ali Teoman; Sari, Elif; Ozakpinar, Hulda Rifat; Eryilmaz, Tolga; Inozu, Emre; Sen, Tulin; Tekdemir, Ibrahim
Abstract : Background and Objective: Different accesses have been used to perform lateral osteotomies in rhinoplasty. All of them have some disadvantages. The aim of this paper was to report a new access to overcome drawbacks of the other techniques in lateral osteotomy during open rhinoplasty. Methods: An anatomical study was designed to search possibility of intranasal extramucosal access (open sky access) for the lateral osteotomy in open rhinoplasty. It was performed directly on the lateral wall of piriform aperture, and then possible advantages of this technique were investigated. Five fixed cadavers were used for this purpose. No drawbacks were observed during procedure in cadavers. Then the same procedure was performed in 23 consecutive rhinoplasty patients. Nineteen operations were primary and 4 operations were secondary. Median oblique osteotomies were added to the procedure in all patients. The mean follow-up was 17 months. Results: Intranasal extramucosal access during lateral osteotomy was easily performed in all patients. Hemorrhage due to angular vessel injury was not occurred during intraoperative period. Edema and ecchymosis was minimal. Intranasal examination did not show any sign for nasal mucosal tearing in all patients. Residual bone spurs or bone irregularities were not observed in any patients. Conclusion: Intranasal extramucosal access that produces precise, predictable, and reproducible aesthetic and functional results could also provide better exposure during lateral osteotomy. Additionally, open sky access minimizes scars because it does not need additional incisions on the skin and mucosa. Protection of the internal periosteum of the nasal bones may be the main advantages of this technique.